The Effect of Green Marketing Mix on Purchase Intention of Body Shop Products in Palembang City - Yuni Adinda Putri (Universitas Islam Lamongan, 2022)
Public awareness of protecting the environment is critical. This is very important because it will have an impact on global warming. This condition has made global consumers aware of environmental sustainability. This creates new demand for environmentally friendly products. Therefore, a new marketing concept that is environmentally sound or commonly referred to as green marketing, has emerged. In this study, the independent variable used is the green marketing mix, and the dependent variable is purchase intention. This type of research is quantitative, with a sample of 96 respondents. The research technique used is non-probability sampling. The results showed that all green marketing mix variables, green product, green price, green place, and green promotion, affected product purchase intention.